DEVELOPMENT OF AN INTEGRATED ETHNOSCIENCE EDUCATIVE MAGAZINE IN THE THEME OF MADURA BAMBOO SHELLS PASTE - Nadifah, Imroatun; Fikriyah, Aida; Ahied, Mochammad; Hadi, Wiwin Puspita; Yasir, Mochammad (Science Education, Institut Agama Islam Negeri Ponorogo, 2023)
Science learning that integrates with local wisdom will make learning run well and meaningfull. This can be realized by developing teaching materials in the form of an educative magazine integrated with ethnoscience on the theme of Madura bamboo shells paste. The purpose of this study was to produce educative magazines and to determine the level of validity, readability of students, and students' responses to the teaching materials developed. This type of research is development using the ADDIE model. The instruments used were media expert validation sheets, material experts, science teachers, readability questionnaires and student responses. The trials carried out were individual trials, small group trials and large group trials. 1) The results showed that the validity of the media aspect was 88.33% and the material aspect was 98.61% with a very valid category. 2) The readability of the students obtained a score in the large group trial, namely 82.32% in the very good category. 3) Student responses obtained a percentage value in the large group trial, namely 85.70% in the very good category. This data shows that flipbook-based educative magazines integrated with ethnoscience on the theme of Madura bamboo shells paste are appropriate for science learning.